Dual-Activity Peptides Act as Bactericides Against Xanthomonas citri subsp. citri In Vitro and Protect Sweet Orange from Infection. - Sanches, Beatriz C P [UNESP]; Martins, Elaine C [UNESP]; Darolt, Josiane C; Dutra, Michele F S [UNESP]; Santos, Talita A; Crusca, Edson [UNESP]; Behlau, Franklin; Marchetto, Reinaldo [UNESP]; Wulff, Nelson A [UNESP] (Scientific Societies, 2025)
One of the prominent bacterial diseases impacting orange production and trade is citrus canker, caused by the bacterium Xanthomonas citri subsp. citri (X. citri). The management of citrus canker involves deploying copper products as a protective measure to control the development of symptoms, which carries the risk of selecting strains that are resistant to copper. The objective of this report was to evaluate four peptides with potential antibiotic activity against X. citri in vitro and in planta. In growth inhibition assays, the peptides Gr01, Guavanin 2, K-13, and Lin1 had an inhibitory effect on X. citri at concentrations below 12.5 µmol liter-1. Minimal bactericidal effects were observed at peptide concentrations of 100 and 50 µmol liter-1 for Lin1 and Guavanin 2, respectively, and 12.5 µmol liter-1 for Gr01 and K-13. Membrane mimetics coupled with fluorescence spectroscopy assays showed that Guavanin 2, Gr01, and K-13, but not Lin1, act by promoting bacterial membrane lysis. Moreover, the Gr01, K-13, and Lin1 peptides triggered a prolonged induction of genes associated with the activation of the jasmonic acid and salicylic acid pathways, suggesting a dual function of these peptides in promoting a priming effect. The severity of citrus canker in plants treated with Gr01, K-13, and Guavanin 2 was 0.2, 0.3, and 0.4 lesions/cm2, respectively. These values were similar to those recorded in plants treated with copper (0.3 lesions/cm2) and significantly lower than the 1.5 lesions/cm2 observed in untreated plants. Gr01 and K-13 peptides are promising dual-activity alternatives in the management of citrus canker.